Development of Measuring Tools For Swimming Physical Tests on Students Physical Education (Department of Physical Education, Sport, Health and Recreation, 2023)
This research produces a practical, valid, and effective application to measure the physical test of swimming. The R&D method was used with a sample of 3rd semester Physical Education students at FKIP Unsri. Data was collected through validation tests, practicality tests, and effectiveness tests using validation sheets, questionnaires, and student applications. The sports physical test measuring instrument in various branches in this study was very valid (83.92%) and feasible to use (average 81.25%). The main finding is the specific application to measure the physical test of swimming sports. The implication is that this application helps coaches, athletes, students, and students in measuring the process and results of swimming training.